Interlayer screening effects in WS2/WSe2 van der Waals hetero-bilayer. (2nd August 2018) - Kumar, Rajeev; Verzhbitskiy, Ivan; Giustiniano, Francesco; Sidiropoulos, Themistoklis P H; Oulton, Rupert F; Eda, Goki
Abstract: Screening plays a fundamental role in determining the quasi-particle band gap and many-body effects of two-dimensional (2D) semiconductors. However, the electronic and optical properties of individual layers in van der Waals (vdW) heterostructures are often assumed to remain unaltered from those of isolated layers. Here, we study band gap renormalization and exciton binding energy changes in WS2 /WSe2 hetero-bilayers using absorption and photoluminescence excitation (PLE) spectroscopy. From the scaling behavior of higher order exciton energies, we estimate the exciton binding energy and quasi-particle band gap of constituent layers in the hetero-bilayer. We show that the band gap and the intralayer exciton binding energy of the constituent layers are reduced by as much as 100 meV and 70 meV, respectively, due to dielectric screening of the adjacent layer. These observations serve as an important step towards implementing rational design criteria for optoelectronic devices based on vdW heterostructures.